Biochemistry - Rawn, J. David (Burlington, MA : Patterson, 1989)
This book is intended for an introductory course taken by students who have had general and organic chemistry.
Part One. Introduction -- Part Two. Protein conformation and function -- Part Three. The generation and storage of metabolic energy -- Part Four. The biochemistry of precursors of macromolecules -- Part Five. Biological information flow.
Includes bibliographical references and index.
Keywords: BIOCHEMISTRY